The Analysis Factors Affecting Students' Willingness to Communicate In EFL Classroom - Mega Syafitri; Munir; Amra Ariyani (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research employed a descriptive qualitative method to explore the primary factors affecting students’ Willingness to Communicate (WTC) in English as a Foreign Language (EFL). The study was conducted through observation, in-depth interviews, and documentation with EFL students and analysed using theories from Macintyre et al.’s (1998) heuristic model of WTC as the theoretical framework. The findings reveal that a complex interplay of individual, social, and pedagogical factors influences WTC. Key internal factors include communicative self-confidence, language anxiety, motivation (both instrumental and integrative), and personality traits such as introversion and extroversion. Students reported greater WTC when interacting with familiar peers, when they perceived the conversation partner as less dominant, or when the topic was familiar and engaging. Linguistic competence, particularly vocabulary and grammar mastery, also significantly impacted their willingness to speak. While the social context emerged as equally influential, students highlighted that peer support, a positive classroom atmosphere, and a non-threatening environment facilitated their WTC, while fear of making mistakes or negative evaluation, especially during formal interactions with lecturers, served as communication barriers. The flexible use of Bahasa Indonesia in combination with English was also noted as a scaffold that helped ease anxiety and improve comprehension. Overall, this study concludes that WTC is not a fixed trait but a dynamic construct shaped by psychological readiness, linguistic ability, interpersonal relationships, and instructional methods. This research should be conducted in a more varied sample. Replicating this study across different regions, educational levels, and learner demographics will help generalize the findings and strengthen the evidence base for best practices in EFL teaching. Besides, Research into how variables such as emotional intelligence, self-efficacy, and language learning beliefs interact with WTC can contribute to more personalized language teaching approaches to investigating students' WTC in the EFL classroom.